Figur Orang Asing pada Lukisan Karya I Ketut Gede Singaraja - Purwita Dewa Gede (Pusat Penelitian Arkeologi Nasional, 2021)
I Ketut Gede Singaraja always portrays figures adopted from the depiction of wayang pattern. It is similar to Wayang Kamasan but more expressive. Aside of painting the local figures, he also painted foreign figures such as Javanese-Muslims, Chinese people, and Europeans. They were narrated as the cultural actors in the life of Singaraja City at the end of the 19th Century. This paper compares those figures, especially their attributes and faces thorugh iconographic studies. The result shows some cultural diversity through figures painted by I Ketut Gede Singaraja. The diversity is a plurality that occurred as a result of cultural unification from the previous period, namely the spice route period. The purpose of this paper is to identify the ethnic foreign figures described by I Ketut Gede Singaraja in his paintings as part of the multicultural life in Singaraja city at the end of the 19th century.